Insights Into Exosomal Non-Coding RNAs Sorting Mechanism and Clinical Application - Qiu, Yi; Li, Peiyao; Zhang, Zuping; Wu, Minghua (Frontiers in Oncology, 2021)
Exosomes are natural nanoscale bilayer phospholipid vesicles that can be secreted by almost all types of cells and are detected in almost all types of body fluids. Exosomes are effective mediators of cell–cell signaling communication because of their ability to carry and transfer a variety of bioactive molecules, including non-coding RNAs. Non-coding RNAs have also been found to exert strong effects on a variety of biological processes, including tumorigenesis. Many researchers have established that exosomes encapsulate bioactive non-coding RNAs that alter the biological phenotype of specific target cells in an autocrine or paracrine manner. However, the mechanism by which the producer cells package non-coding RNAs into exosomes is not well understood. This review focuses on the current research on exosomal non-coding RNAs, including the biogenesis of exosomes, the possible mechanism of sorting non-coding RNAs, their biological functions, and their potential for clinical application in the future.